Resin-based Brake Pad with Fleece Fiber and Its Mechanical Properties (http://dx.doi.org/10.31427/IJSTT.2022.5.2.2, 2022)
Fleece has strong and good fiber characteristics, which are needed to manufacture brake pads. This study aims to analyze the fleece performance as a friction component material in brake pads. The fleece was initially pre-treated by heating for 4 hours at 150°C and cut into 2 mm sizes. The epoxy resin and hardener were mixed with a ratio of 1:1. The 0.5 g pre-treatment fleece was added to the resin mixture, so the total mass of the resin-fleece mixture was 12.5 g. The mixture was then molded into a cube mold (dimensions of 2.5 × 2.5 × 2.5 cm). The brake pad was dried at room temperature for a day. The characterizations were done using the compressive strength and puncture strength test. The results showed that the fleece brake pad has good mechanical characteristics, demonstrated by the pressure of 215 MPa, which can still be held by the surface of the fleece brake pad. The puncture test showed an average puncture of 76.43%. Overall, the fleece shows good performance on the brake pads. Fleece has many minerals that make it as powerful fiber characteristics and prospective as a friction component material on the brake pads. This research is expected to provide new information about organic materials for friction materials in brake pads.